GLP-1/GLP-1R Signaling Regulates Ovarian PCOS-Associated Granulosa Cells Proliferation and Antiapoptosis by Modification of Forkhead Box Protein O1 Phosphorylation Sites - Zhihua Sun; Peiyi Li; Xiao Wang; Shuchang Lai; Hong Qiu; Zhi Chen; Shidi Hu; Jie Yao; Jie Shen (International Journal of Endocrinology)
As the major cause of female anovulatory infertility, polycystic ovary syndrome (PCOS) affects a great proportion of women at childbearing age. Although glucagon-like peptide 1 receptor agonists (GLP-IRAs) show therapeutic effects for PCOS, its target and underlying mechanism remains elusive. In the present study, we identified that, both in vivo and in vitro, GLP-1 functioned as the regulator of proliferation and antiapoptosis of MGCs of follicle in PCOS mouse ovary. Furthermore, forkhead box protein O1 (FoxO1) plays an important role in the courses. Regarding the importance of granulosa cells (GCs) in oocyte development and function, the results from the current study could provide a more detailed illustration on the already known beneficial effects of GLP-1RAs on PCOS and support the future efforts to develop more efficient GLP-1RAs for PCOS treatment.